Structural Health Monitoring for Sustainable and Resilient Infrastructure Management - Dalton, Sarah; Atamturktur, Sez; Juang, Hsein (International Journal of Building, Urban, Interior and Landscape Technology, 2013)
This manuscript introduces a methodology to build a new framework, Structural Life-Cycle Assessment (S-LCA), for quantifying the structural sustainability and resiliency of built systems. This research brings together techniques and concepts from two distinct disciplines: Structural Health Monitoring (SHM) of Civil Engineering and Life Cycle Assessment (LCA) of Environmental Engineering to construct the aforementioned S-LCA charts. The intellectual innovations of this manuscript lie in the advancement in infrastructure management techniques through the development of S-LCA charts, which can be useful as an infrastructure monitoring and decision-making tool, for quantifying the structural sustainability and resiliency of built systems. Such a tool would be of great use in aiding infrastructure managers when prescribing maintenance and repair schemes. Moreover, a quantitative, real-time evaluation of structural damage after a disaster would support emergency managers in resource allocation. The manuscript integrates science based modeling and simulation techniques with advanced monitoring and sensing tools, resulting in scientifically defendable, objective and quantitative metrics of sustainability and resiliency to be used in infrastructure management.